Pemanfaatan Layanan E Book Oleh Pemustaka di Perpustakaan IAIN Kediri - Moch. Basit Aulawi (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2021)
This research aims to see the extent to which e-book services at IAIN Kediri have been utilized by musicians. The theory used is ebook and Pustaka services. Using a qualitative approach, this study concluded that ebook services are very useful for respondents. The majority of users know the collection over the internet. Pemustaka is able to browse e-book collections independently without using the help of librarians. Pemustaka explores the collection of e-books through a google search engine and web library. The behavior of the user in using the e-book service is: directly read on the screen, download the e-book file, saved as a private collection, in print., respondents make use of the collection of e-books for personal collections and references. While the information in the e-book is used by respondents to create articles, and add knowledge.